PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.2 SMP NEGERI 9 PEKANBARU - Afriyeni, Kartika; ', Syofni; ', Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is low of mathematics learning outcomes of class VII.2 SMPN 9 Pekanbaru in second semester of the 2015/2016 academic year. Subject of this research are  36 students, consist of 18 male and 18 female student with heterogenous level of academic capabilities. The type of this research is the Classroom Action Research that has purpose to improve the learning proses and to increase student’s mathematic learning outcomes with applied the cooperative learning with Think Pair Square Structural Approach.  This research consist of two cycles that each cycle composed of 4 stages, such as planning, implementation, observation and reflection. At every end of a cycle, math achievement test will be held. The research instrument consists of learning devices that involve Syllabus, Lesson Plan and Student Worksheet, and instrument data collector that involve the observation sheet and math achievement test. Observation sheets is analyzed by narrative descriptive analysis and math achievement test analyzed by statistic descriptive analysis. The action is successful if the learning process covenient with the Lesson Plan and the number of students who achieve the score of Minimum Mastery Criteria increase in math achievement test I and II. Most of students were excited and active in learning process, as while they were doing the steps of learning, presenting Student Worksheet, responding to friend’s presentation and giving the conclusion of learning. Based on the data analysis, the percentage of students who achieve Minimum Mastery Criteria before the action is as much as 41.67% and at first cycle as much as 55.55% and at second cycle as much as 80.55%. The result of the research show that, the learning process has improved and the student’s mathematic learning outcomes also increased after applying the Cooperative Learning with Think Pair Square Structural Approach.                                                                                                                                              Key Words:  Classroom Action Research, Cooperative Learning, Think Pair Square Structural Approach, Learning Process, Student Mathematic Learning Outcomes